Scyliorhinus ugoi, a new species of catshark from Brazil (Chondrichthyes: Carcharhiniformes: Scyliorhinidae) - Soares, Karla D. A.; Gadig, Otto F. B.; Gomes, Ulisses L. (Zootaxa, 2015)
A new species of catshark (Carcharhiniformes, Scyliorhinidae), Scyliorhinus ugoi sp. nov., is described from off Northeastern and Southeastern Brazil. The new species is closest to the Scyliorhinus haeckelii/besnardi group and S. hesperius but differs in background coloration, head width, sexual maturity, and in cranial and body proportions.